Applying a Mad Studies Framework to Opera: Poulenc’s Dialogues des Carmélites - Simonot-Maiello, Colette (Intersections, 2020)
Multiple readings of madness are examined in Poulenc’s opera Dialogues des Carmélites (1957) through the framework of mad studies. Several layers of madness can be found in this work: individual lived experiences of madness, the history of mental illness in France during and after the French Revolution, and the cultural metaphor of hysteria as social degeneration, as articulated by Micale. Close readings of two scenes with a discussion of their musical features are included: the first prioress’s death (act 1, scene 4) and the final scene at the guillotine (act 3, scene 4).